Ferroelectric Extended Nanofluidic Channels for Room‐Temperature Microfuel Cells. Issue 9 (17th June 2019) - Pihosh, Yuriy; Kazoe, Yutaka; Mawatari, Kazuma; Seo, Hangyeol; Tabata, Osamu; Tsuchiya, Toshiyuki; Kitamura, Kenji; Tosa, Masahiro; Turkevych, Ivan; Kitamori, Takehiko
Abstract: Integration of fuel cells into microfluidic devices requires development of innovative proton conductors. Conventional Nafion membranes are incompatible with planar‐type microfluidic devices and require a high operation temperature of over 100 °C to achieve rapid proton transfer. In contrast, glass nanochannels (NCs) work as proton conductors even at room temperature and can be seamlessly integrated into microfluidic devices, which in turn makes microfuel cells (µFCs) attractive for a wide range of practical applications, such as power sources for ultrasmall autonomous electronics and chemo‐ or biosensors. However, the conductivity of NCs is limited by their small cross‐sectional area. It is revealed that spontaneous polarization of lithium niobite (LiNbO3 ) used as the NC material enhances a surface charge of a SiO2 layer formed on LiNbO3 and induces a fast proton transfer in water in the NCs. It is demonstrated that a µFC containing the LiNbO3 NCs demonstrates a proton diffusion coefficient that is 1.8 times higher than that of a reference device with bare glass NCs. In addition, such a µFC achieves a remarkable power output of up to ≈54 mW cm −2 at room temperature, which is 1.4 times higher than that of the similar device with bare glass NCs. Abstract : Nanochannels and ferroelectric LiNbO3 are used to create a high‐performance room‐temperature proton conductor. Spontaneous polarization of LiNbO3 changes the NC surface potential, attracting protons to the NC surface and raising their mobility. A µFC with LiNbO3 NCs achieves a remarkable power output of up to ≈54 mW cm −2, which is 1.4 times higher than bare glass NCs.